2013
DOI: 10.1039/c3mt00186e
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the biological response of mouse liver (Mus musculus) exposed to As2O3 based on integrated -omics approaches

Abstract: Organic and inorganic mass spectrometries were used to investigate the biochemical response of mice (Mus musculus) to inorganic arsenic exposure using liver as the target organ. The toxicological effects of trivalent inorganic arsenic after oral administration (3 mg kg(-1) body weight and per day) were investigated over a period of 7 days using metallomics, metabonomics and redox proteomics approaches. Size-exclusion chromatography (SEC) with ICP-MS detection was combined with anion exchange chromatography (AE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
49
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 81 publications
5
49
0
Order By: Relevance
“…To acquire MS/MS spectra, N 2 was used as collision gas. Gas chromatography-mass spectrometry (GC-MS) analysis was also applied to mice plasma, as previously described (Garcia-Sevillano et al, 2013). Derivatizing agents, methoxylamine hydrochloride and N-methyl-N-(trimethylsilyl) trifluoroacetamide containing 1% trimethylchlorosilane, were obtained from Sigma-Aldrich.…”
Section: Analysis Of Sample Extracts By Direct Infusion-mass Spectrommentioning
confidence: 99%
“…To acquire MS/MS spectra, N 2 was used as collision gas. Gas chromatography-mass spectrometry (GC-MS) analysis was also applied to mice plasma, as previously described (Garcia-Sevillano et al, 2013). Derivatizing agents, methoxylamine hydrochloride and N-methyl-N-(trimethylsilyl) trifluoroacetamide containing 1% trimethylchlorosilane, were obtained from Sigma-Aldrich.…”
Section: Analysis Of Sample Extracts By Direct Infusion-mass Spectrommentioning
confidence: 99%
“…Through a cross-omics method, it is demonstrated that the major metabolic consequences of acute toxicity of aflatoxin B1, one of the well-known hepatotoxic mycotoxin, are associated with gluconeogenesis and lipid metabolism pathways 9 . Moreover, inorganic arsenic methylation in mouse liver may be saturated under chronic exposure to the element based on an integrated-omics approach 10 . The toxicity mechanism of another hepatotoxic compound EMD 335823 was also elucidated by using modern omics technologies, from which the liver pathologies are linked to deregulated PPARa signaling, glucose metabolism, and fatty acid metabolism 11 .…”
mentioning
confidence: 99%
“…Despite the advantages of coupling separations techniques to mass spectrometry (e.g., matrix effects and isobaric interferences reduction), a number of studies recommend to use direct infusion of samples to mass spectrometer without any previous separation. This approach has been recently proposed in toxicological studies of mice [12,13,15,16] using high mass resolution analyzers, such as hybrid systems triple quadrupoletime-of-flight (QqQ-TOF). Under suitable experimental conditions, MS peak intensities are proportional to metabolite concentration and thus can be used to look for biomarkers related to toxic metal exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Toxicometabolomics combines the use of: (i) experiment exposure to xenobiotics; (ii) multivariate pattern recognition based on metabolic profiling capabilities of multiple methodologies, including gas chromatography-mass spectrometry (GC-MS) [10], liquid chromatography-mass spectrometry (LC-MS) [11], direct infusion-mass spectrometry (DIMS) [11][12][13][14][15][16] and nuclear magnetic resonance (NMR) spectroscopy [8,9,17]; and (iii) chemometric analysis. Despite the advantages of coupling separations techniques to mass spectrometry (e.g., matrix effects and isobaric interferences reduction), a number of studies recommend to use direct infusion of samples to mass spectrometer without any previous separation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation